India-Singapore Innovation Hub : New Impetus for Economic Cooperation - Choudhury, Rahul (2018)
A new innovation hub launched in Singapore during Prime Minister Narendra Modi’s recent visit will facilitate collaboration between Indian and Singapore enterprises by being a bridge in their start-up landscape.